A Rare Occurrence of Solid Gynecological Malignancy Synchronous with Hematological Malignancy: Rare Case and Review of Literature - Gupta, Rubi; Dave, Pariseema; Patel, Bijal; Shukur, Remi Abdul (Indian Journal of Medical and Paediatric Oncology, 2023)
A synchronous solid and hematological malignancy is an uncommon condition in which a patient develops two or more primary cancers, one of which is a solid malignancy and the other one is a hematological malignancy, within 6 months of primary cancer diagnosis. The most common histology in solid malignancies is gastrointestinal adenocarcinoma, which coexists with the lymphoma subtype diffuse large B-cell lymphoma (DLBCL). Here, we report an extremely rare combination of serous carcinoma of the ovary synchronous with lymphoma of DLBCL subtype. A woman aged 52 years presented with an abdominal mass and abdominal pain for a short duration of 15 days. She was evaluated using clinical, radiological, and biochemical parameters. She was diagnosed with non-Hodgkin lymphoma by tru-cut biopsy from a bony lytic lesion and ovarian cancer by staging laparotomy. R-CHOP (rituximab, cyclophosphamide, doxorubicin hydrochloride, vincristine, and prednisolone) chemotherapy for lymphoma and staging laparotomy for persistent adnexal mass resulted in complete remission of both ovarian cancer and lymphoma. She received paclitaxel and carboplatin-based postoperative chemotherapy as an adjuvant for ovarian cancer.
Keywords: synchronous multiple primary malignancies; lymphoma; serous ovarian cancer